TOPAZ simulator on mesh and torus network - Rahman, M.M. Hafizur; Yahya Hag, Ala Ahmed; Mohd. Nor, Rizal; Sembok, Tengku Mohd (2014)
In this paper, we have evaluated the dynamic communication performance of the mesh and torus networks using a open source TOPAZ simulator using virtual cut through switching under uniform traffic pattern. It is found that the torus network yields low latency and high throughput than that of mesh network. Therefore, The dynamic communication performance of the torus network is better than that of the mesh network. The well known phenomenon is justified using a new open source simulator, TOPAZ simulator.